Factoriser au maximum les expressions suivantes.

A = (x - 5)( x + 2) + ( x - 5)( x - 7)

B = x² - 10x

C = x( x + 2) + 3x

D = ( x + 2)( x + 1)-2( x +1)

E = ( x + 3)( x - 2)-( x -2)(2x + 1)

F = (2x + 3)²-( x+ 1)(2x + 3)

G= x² - 9

H = x² - 6x + 9

I = 4x² - 20x + 25

K = (2x - 1)² - ( x + 1)²

L = (3x - 1)² - 25

M = 9x² + 6x + 1

Merci d'avance pour vos réponses !

1

Réponses

2014-08-27T17:05:07+02:00
A=(x-5)[(x+2)+(x-7)]
A=(x-5)(2x-5)

B=x²-10x=x(x-10)

C=x(x+2)+3x=x(x+2+3)=x(x+5)

D=(x+2)(x+1)-2(x+1)
D=(x+1)[(x+2)-2]
D=x(x+1)

E=(x+3)(x-2)-(x-2)(2x+1)
E=(x-2)[(x+3)-(2x+1)]
E=(x-2)(2-x)
E=-(x-2)²

F=(2x+3)²-((x+1)(2x+3)
F=(2x+3)[(2x+3)-(x+1)
F=(2x+3)(x+2)

G=x²-9=x²-3²=(x+3)(x-3)

H=x²-6x+9=(x-3)²

I=4x²-20x+25=(2x-5)²

K=(2x+1)²-(x+1)²=(2x+1+x+1)(2x+1-x-1)=x(3x+2)

L=(3x-1)²-25=(3x-1+5)(3x-1-5)=(3x+4)(3x-6)

M=9x²+6x+1=(3x+1)²